1988
DOI: 10.1021/bi00418a025
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and physical characterization of acceptors for dendrotoxin and .beta.-bungarotoxin from synaptic membranes of rat brain

Abstract: Dendrotoxin (DTX), an Mr 7000 convulsant polypeptide from the venom of Dendroaspis angusticeps, or its facilitatory homologues act through blockade of certain voltage-sensitive K+ currents in a variety of neurons. High-affinity acceptors for DTX have been demonstrated in synaptic plasma membranes of rat or chick brain, and a fraction of these avidly bind beta-bungarotoxin (beta-BuTX), a presynaptically active protein whose lighter B polypeptide is homologous to this toxin. Extraction of rat synaptic plasma mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 39 publications
5
35
0
Order By: Relevance
“…3 B), attenuation of specific binding attaining about 80% at 1 pM, with an ICsO of about 60 nM ('251-DTX concentration = 0.7 nM). This increased level of inhibition is in good agreement with that observed for solubilized DTX acceptors, again using imidazole buffer [33,34]; in both cases, the notably extended competition curves are consistent with the kinetic heterogeneity identified by direct binding of 1251-fl-BuTX under these conditions (Fig. 2).…”
Section: Dtx and P-butx Interact Primarily Via Distinct Binding Sitessupporting
confidence: 87%
“…3 B), attenuation of specific binding attaining about 80% at 1 pM, with an ICsO of about 60 nM ('251-DTX concentration = 0.7 nM). This increased level of inhibition is in good agreement with that observed for solubilized DTX acceptors, again using imidazole buffer [33,34]; in both cases, the notably extended competition curves are consistent with the kinetic heterogeneity identified by direct binding of 1251-fl-BuTX under these conditions (Fig. 2).…”
Section: Dtx and P-butx Interact Primarily Via Distinct Binding Sitessupporting
confidence: 87%
“…To demonstrate that P/Q-type VGCCs were specifically reduced and that other channels or receptors were not reduced, we performed binding assays using 125 I--dendrotoxin (2,000Ci/mmol; Amersham, Buckinghamshire, UK) which is a voltage-gated potassium channel (VGKC) blocker, as previously described. 15 It has been demonstrated that VGKC was enriched in the molecular layer of the rat cerebellum. …”
Section: Binding Studiesmentioning
confidence: 99%
“…Moreover, in the brain each toxin inhibits the binding of the other toxins (Bidard et al, 1987a;Rehm et al, 1988;Breeze and Dolly, 1989;Schweitz et al, 1989a;Brlu et al, 1990). Solubilization of the toxin binding sites with detergent does not prevent the mutual interaction between these sites and, furthermore, the toxin binding sites copurify (Rehm and Betz, 1984;Rehm et al, 1988;Black et al, 1988). Thus, the dendrotoxins, MCD, CTX and /?-BTX bind to the same (b) the apparent molecular mass of the glycosylated subunit determined by SDSjPAGE changes with the percentage of the gels (i.e.…”
Section: Proteins Whlch Bind the K + Channel Toxinsmentioning
confidence: 99%
“…The fact that both subpopulations have high-affinity sites for DTXl is in accord with the consistent finding that there are more high-affinity a-DTX and DTXI sites than high-affinity 8-BTX sites in brain membranes (Rehm and Lazdunski, 1988 b;Breeze and Dolly, 1989). It also explains why P-BTX is a less efficient inhibitor of a-DTX binding than a-DTX is for p-BTX binding Black et al, 1988;Brau et al, 1990).…”
Section: Dmb Protein Is Heterogenousmentioning
confidence: 99%
See 1 more Smart Citation